New media: dinamika neo-rasisme di Twitter - Hasnun Jauhari Ritonga; Ahmad Sampurna; Arya Fandhy (Faculty of Communications Science, Dr. Soetomo University, 2024)
This research aims to understand and evaluate the climate of neo-racism in Indonesia, focusing on discriminatory experiences within a heterogeneous society. The study employs a qualitative and content analysis approach, utilising 7.097 tweets about racism as primary data and a literature review as secondary data. In the analysis process, the researchers used Netlytic software to identify patterns or trends of racism on Twitter. The obtained data were then reconstructed to ensure validity. Subsequently, the data were reduced, presented, and concluded to identify the racism climate on Twitter accurately. The findings of this study reveal that the dynamics of neo-racism on Twitter reflect deep-seated issues regarding society's understanding of racism. In Indonesia, the legacy of colonialism and identity politics exacerbates this situation, while regulations and law enforcement remain ineffective in addressing this issue. Analysis of netizens' interactions shows that much content focuses on accusations and validation without concrete solutions. Therefore, comprehensive efforts involving robust regulation, social media ethics education, and cooperation between the government, social media platforms, and the community are necessary. These efforts aim to create an inclusive environment that respects diversity, while also building collective awareness of the importance of tolerance and eliminating discrimination.